The Phendo Project: How FemTech Is Advancing Endometriosis Research and Women’s Health - Jenny Castillo Cato (Journal of Medical Internet Research, 2026)
Abstract FemTech continues to evolve and advance despite persistent research and funding gaps. In this News and Perspectives article, JMIR Correspondent Jenny Castillo Cato reports on an innovative, cross-disciplinary research project targeting endometriosis and implications for the broader FemTech movement.